2016
DOI: 10.1128/jvi.00684-16
|View full text |Cite
|
Sign up to set email alerts
|

HIV Maintains an Evolving and Dispersed Population in Multiple Tissues during Suppressive Combined Antiretroviral Therapy in Individuals with Cancer

Abstract: While combined antiretroviral therapy (cART) can result in undetectable plasma viral loads, it does not eradicate HIV infection. Furthermore, HIV-infected individuals while on cART remain at an increased risk of developing serious comorbidities, such as cancer, neurological disease, and atherosclerosis, suggesting that during cART, tissue-based HIV may contribute to such pathologies. We obtained DNA and RNA env, nef, and pol sequences using single-genome sequencing from postmortem tissues of three HIV ؉ cART-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…Lorenzo-Redondo et al (24) recently reported finding genetic changes in HIV proviruses [proviruses are the integrated form of retrovirus DNA (27)] in the 6 months following the initiation of cART, leading to the generation of populations of HIV proviruses in tissues that were distinct from the population of HIV proviruses in PBMCs. That report and others (23,25,28,29) suggested that HIV replication that was restricted to tissue sanctuary sites resulted in the generation of markedly different populations of HIV proviruses in blood and tissues after prolonged cART. In contrast, if the reservoir consists of cells (or their descendants) that were infected before cART was initiated, there will be no additional genetic changes in the populations of proviruses during cART.…”
Section: Introductionmentioning
confidence: 88%
“…Lorenzo-Redondo et al (24) recently reported finding genetic changes in HIV proviruses [proviruses are the integrated form of retrovirus DNA (27)] in the 6 months following the initiation of cART, leading to the generation of populations of HIV proviruses in tissues that were distinct from the population of HIV proviruses in PBMCs. That report and others (23,25,28,29) suggested that HIV replication that was restricted to tissue sanctuary sites resulted in the generation of markedly different populations of HIV proviruses in blood and tissues after prolonged cART. In contrast, if the reservoir consists of cells (or their descendants) that were infected before cART was initiated, there will be no additional genetic changes in the populations of proviruses during cART.…”
Section: Introductionmentioning
confidence: 88%
“…In general, most studies aiming to characterize HIV DNA reservoirs in persons with HIV (PWH) have necessarily focused on blood, with a few other compartments that are relatively easy to sample such as the gut, through endoscopy (5,10,11,24), the genital tract, through genital secretions (12,(25)(26)(27)(28)(29)(30), or the CNS, through cerebrospinal fluid (CSF) (31)(32)(33)(34)(35)(36)(37). Of note, one study in PWH diagnosed with cancer allowed the analysis of HIV reservoirs in selected anatomic tissues collected during autopsy (38,39). More recently, De Scheerder et al investigated the origins of HIV rebound, and although this study was limited by the number of anatomical sites, they showed that viral rebound originated from diverse cellular and tissue reservoirs (40).…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Many common viruses, including influenza ( Hamada et al 2012 ; Lakdawala et al 2015 ; Sobel Leonard et al 2017 ), HIV and related viruses ( Ait-Khaled et al 1995 ; Rose et al 2016 ; Feder et al 2017 ), and cytomegalovirus (CMV) ( Renzette et al 2013 ), have been identified as existing as separate subpopulations within a host, which may exhibit distinct viral diversity. In so far as mathematical models of viral evolution fit a model population to data from genome sequencing, failure to consider this structure may lead to overconfidence in the extent to which a model reproduces the true within-host viral population.…”
Section: Introductionmentioning
confidence: 99%